Presenting in English :how to give successful presentations /Mark Powell. - Powell, Mark.
Resulting from research into what really makes presentations so successful, this course s approach combines the language and skills needed to give effective presentations. It is aimed at intermediate to upper intermediate students and employs simple rhetorical techniques.